Comparison of two total RNA extraction protocols from CHO-K1 cells for RT-PCR: cutoff cost for researchers - Packeer Mohamed, Vasila; Hashim, Yumi Zuhanis Has-Yun; Amid, A.; Mel, Maizirwan (IIUM Press, 2014)
Various methods have been described to extract RNA from adherent mammalian cells. RNA isolation in conjunction with reverse transcription polymerase chain reaction (RT-PCR) is a valuable tool used to study gene expression profiling. This approach is now being used in mammalian cell bioprocessing to help understand and improve the system. The objective of this study was to compare and determine the most suitable RNA extraction method for CHO-K1 cells in a setting where a relatively large amount of samples was involved. Total RNA was extracted using Total RNA purification kit (without DNase treatment; Norgen, Canada) and RNeasy mini kit (with DNase treatment; Qiagen, USA) respectively. The extracted RNA was then reverse transcribed, and the cDNA was subjected to PCR-amplifying 18S. Yield from RNeasy kit was significantly higher (0.316 ± 0.033 μg/μl; p=0.004) than Total RNA purification kit (0.177 ± 0.0243 μg/μl). However, RNA purity for both methods was close to 2.0 and there was no significant difference between the methods. Total RNA purification kit is less expensive than RNeasy kit. Since there is no DNase treatment step in the former, extraction time for RNA is shorter. When the extracted RNA was subjected to RT-PCR, both methods were able to show detection of 18S at 219 bp. Therefore, this study demonstrates that both protocols are suitable for RNA extraction for CHO-K1 cells. RNeasy mini kit (Qiagen) is recommended if higher yields is the primary concern and Total RNA Purification kit (Norgen) is recommended if time and cost are concerned.